Partner smoking characteristics: Associations with smoking and quitting among blue-collar apprentices - Okechukwu, Cassandra A. (2010)
BACKGROUND: Studies suggest that the social context of blue-collar workers contribute to their low smoking cessation rates. However, little is known on the effect of partner smoking and requests to quit on workers’ cessation attempts. METHODS: Using data from a longitudinal smoking cessation intervention, multivariable logistic regression models were constructed to investigate the association of partner smoking characteristics with cessation among blue-collar apprentices. RESULTS: Smokers were more likely to have partners who smoke (OR 13.06; 95% CI 8.52-20.01). Partner's request to quit was associated with higher odds of smoking cessation at one month (OR 3.74; 95% CI 2.49-5.63) and six months (OR 1.90; 95% CI 1.06-3.41) post-intervention. Having a partner who smoked was associated with lower odds of smoking cessation at one month (OR 0.41; 95% CI 0.27-0.62), but not six months post-intervention. CONCLUSIONS: Results suggest that smoking cessation interventions that include partner support might improve cessation among blue-collar smokers.